when the future reaches us. on the sixtieth anniversary of the creation of the Universidad Centroccidental Lisandro Alvarado (UCLA) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2022)
In the 20th century, more changes took place in the life of the human being than during the thousand years of the Roman Empire or the long period of the Stone Age. These mutations were due more to the discoveries of science and the inventions of technology than to the two world wars, totalitarianism, genocide and ethnocide that shocked humanity in that century or to the Cold War that divided the world. between two incompatible and opposed military-industrial blocs, which threatened each other with the triumph of one over the destruction of the other. The greatest techno-scientific changes were brought by the so-called information technologies (IT), in which Venezuela was a pioneer in Latin America with the installation of computers and the creation of university degrees decades before the rest of the continent. The Lisandro Alvarado Centroccidental University has played a very important role with the creation of cutting-edge careers and IT research centers, long before other universities in the country and in Latin America. But the socioeconomic and political crisis that the country has been suffering and the Venezuelan university in particular, has stopped our development, to the point that it even threatens the disappearance of the national university, and its future is grim and ominous. More changes are coming and this is prefigured by the opinions of the best qualified experts in the world. Are we prepared to face them? This article analyzes some of the most relevant aspects of the possible and complex scenarios that await us so that we can reinvent our universities before: the future catches up with us!
Keywords: 20th century; changes; socioeconomic and political crisis; information technologies; university